2017
DOI: 10.4103/ija.ija_712_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analgesic efficacy of caudal dexmedetomidine versus caudal tramadol with ropivacaine in paediatric infraumbilical surgeries: A prospective, randomised, double-blinded clinical study

Abstract: Background and Aims:Caudal epidural analgesia is commonly practised regional block technique in children undergoing infraumbilical surgeries but has a short duration of action after single shot local anaesthetic injection. The aim of this study was to compare ropivacaine 0.25% with dexmedetomidine and tramadol in caudal anaesthesia in paediatric infraumbilical surgeries.Methods:In a randomised, prospective, double-blinded study, sixty children (1–8 years) belonging to American Society of Anesthesiologists’ phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
1
27
1
Order By: Relevance
“…The study by Gupta and Sharma (15) investigated the addition of 2 mg/kg tramadol versus 2 µg/kg dexmedetomidine to caudal ropivacaine 0.25% administered preoperatively in children who were candidates for infra-umbilical surgery under general anesthesia. The results indicated that the addition of dexmedetomidine, as compared to tramadol, induced prolonged analgesia, but changes in the heart rate and mean BP before and after the block, as well as side effects, were alike (15). Notwithstanding, although adequate analgesia (FLACC score < 4) existed in both groups within the first four hours after the surgery, the analgesia decreased rapidly in the tramadol group afterward.…”
Section: Discussionmentioning
confidence: 88%
“…The study by Gupta and Sharma (15) investigated the addition of 2 mg/kg tramadol versus 2 µg/kg dexmedetomidine to caudal ropivacaine 0.25% administered preoperatively in children who were candidates for infra-umbilical surgery under general anesthesia. The results indicated that the addition of dexmedetomidine, as compared to tramadol, induced prolonged analgesia, but changes in the heart rate and mean BP before and after the block, as well as side effects, were alike (15). Notwithstanding, although adequate analgesia (FLACC score < 4) existed in both groups within the first four hours after the surgery, the analgesia decreased rapidly in the tramadol group afterward.…”
Section: Discussionmentioning
confidence: 88%
“…To manage post-operative pain in pediatric lower abdominal surgery, tramadol and dexmedetomidine were separately added to caudal ropivacaine, and the results showed that the combination of caudal ropivacaine with dexmedetomidine had longer analgesia than its combination with tramadol, but the side effects were similar in the two groups (27). In our study, there existed no third group for further comparison, but it could be a good topic for future research.…”
Section: Discussionmentioning
confidence: 78%
“…Gupta et al [24] reported that 14 patients out of 30 patients had sedation in tramadol group when compared to butorphanol group in epidural analgesia. However, Gupta et al [25] in their study comparing the effect of adding either dexmedetomidine or tramadol to ropivacaine in caudal anesthesia in pediatric, they reported that the level of sedation in tramadol group was generally less than 2. Also, Results from Swathi et al [26] reported a lower sedation score.…”
Section: Discussionmentioning
confidence: 98%